Klasifikasi Penerima Bantuan Pangan Non Tunai Menggunakan Metode Decision Tree - Nopi Purnomo; Sarjon Defit; Y Yuhandri (Jurnal Informasi dan Teknologi, 2021)
Non-Cash Food Assistance is one of the government programs that has changed its name from the RASKIN or RASTRA program which is given to poor families every month by providing an electronic account to buy food at a seller that has been determined by the village government in collaboration with Bank Mandiri. The food assistance given to the beneficiary families is a form of government concern in accordance with the criteria determined by the Ministry of Social Affairs of the Republic Indonesia. The problem that often occurs in the Cipang Kiri Hulu Village Government was the difficulty in determining families who deserve to be given the non-cash food assistance in every year, so that it can cause messy and also protests from the people due to the large number of beneficiary families who are not on target. This study was conducted to classify families who receive the non-cash food assistance so that the results of this study can be used as a reference in making decisions whether appropriate or not to receive the non-cash food assistance in Cipang Kiri Hulu Village. The method that used was classification with the Decision Tree C4.5 Algorithm by using 14 attributes. The data used in this study was data from observations at the research location and interviews directly at the homes of families who received the non-cash food assistance in 2021 where there were 62 population data that have been presented in the csv file. The analysis of this study used the Rapid Miner Software version 9.5.001. The result of this research was to get 3 Rules. The rule was obtained from the final result of the decision tree's form.